Modification of gas condensate gasoline by single atomic alcohols with the use of cavitation - Sergey Kudryavtsev (PC Technology Center, 2021)
The process of modification of gas condensate gasolines with monohydric alcohols with subsequent cavitation treatment of these mixtures has been investigated. The expediency of using alcohol additives in fuels and the relevance of introducing into gasoline production such chemical technologies that use cavitation processing of raw materials and selective energy supply to the reaction zone have been substantiated. The expediency of the production of high-octane gasolines on the basis of a combination of the processes of mechanical mixing of hydrocarbon gasolines with alcohols and the processes of cavitation treatment of alcohol-gasoline mixtures is also substantiated. The description of the laboratory setup and the experimental methodology is given. The influence of the intensity of cavitation treatment on the increase in the octane number is studied and it is proved that there is some optimal intensity at which a constant value of the octane number of the mixture is achieved.